2002
DOI: 10.1067/mva.2002.121068
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of type 2 endoleaks after endovascular repair of abdominal aortic aneurysms: Comparison of transarterial and translumbar techniques

Abstract: The transarterial embolization of inferior mesenteric arteries for the repair of type 2 endoleaks is ineffective and should not be performed. Direct translumbar embolization of the endoleak is effective in the elimination of type 2 leaks and should be the therapy of choice when aggressive endoleak management is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 17 publications
4
111
0
1
Order By: Relevance
“…This is thought to be the reason for the lower recurrence rate among translumbar embolizations in Baum's study. 12 In the case presented here, the endoleak recurred despite transarterial embolization of the endoleak and the feeding vessel.…”
Section: Case Reportmentioning
confidence: 98%
See 1 more Smart Citation
“…This is thought to be the reason for the lower recurrence rate among translumbar embolizations in Baum's study. 12 In the case presented here, the endoleak recurred despite transarterial embolization of the endoleak and the feeding vessel.…”
Section: Case Reportmentioning
confidence: 98%
“…Baum et al demonstrated a very high endoleak recurrence rate when only the feeding artery was embolized using a transarterial approach. 12 Translumbar embolization allows for embolization of the endoleak itself. This is thought to be the reason for the lower recurrence rate among translumbar embolizations in Baum's study.…”
Section: Case Reportmentioning
confidence: 99%
“…Although conservative management of type 2 endoleaks is recommended in suitable candidates, endovascular treatments are indicated in cases of persistent endoleaks or expansion of the aneurysm [1,4]. However, even with this technique, it is often difficult to completely embolize the endoleak [3][4][5]. Here we report a case of type 2 endoleak with three feeding and two draining arteries that was successfully embolized using the direct translumbar approach.…”
Section: Introductionmentioning
confidence: 98%
“…However, some of these patients when followed up in the long term were found to have late AAA expansion after embolization, leading Sarac et al to conclude that coil embolization alone may not be the best procedure for long term efficacy [20]. Baum et al recommend direct translumbar endoleak embolization preferentially over transarterial endoleak embolization after T2L is confirmed by angiography [21].…”
Section: Journal Of Vascular and Endovascular Surgery Issn 2573-4482mentioning
confidence: 99%